Macrophage Wnt7b is critical for kidney repair and regeneration - Lin, Shuei-Liong (National Academy of Sciences, 2010)
Macrophages are required for tissue homeostasis through their role in regulation of the immune response and the resolution of injury. Here we show, using the kidney as a model, that the Wnt pathway ligand Wnt7b is produced by macrophages to stimulate repair and regeneration. When macrophages are inducibly ablated from the injured kidney, the canonical Wnt pathway response in kidney epithelial cells is reduced. Furthermore, when Wnt7b is somatically deleted in macrophages, repair of injury is greatly diminished. Finally, injection of the Wnt pathway regulator Dkk2 enhances the repair process and suggests a therapeutic option. Because Wnt7b is known to stimulate epithelial responses during kidney development, these findings suggest that macrophages are able to rapidly invade an injured tissue and reestablish a developmental program that is beneficial for repair and regeneration.